Obesity and risk of hearing loss in the middle-aged and elderly: a national cohort of Chinese adults - Chen Zhang; Weiwei Wang; Xiaotian Chang; Siyan Zhan; Shengfeng Wang; Lei Feng; Yongfeng Song (BMC Public Health, 2023)
Abstract Background The relationship between obesity and hearing loss among the middle-aged and older population remained unclear. Moreover, few studies have focused on the impact of gender on this association. Methods This cohort study extracted the data from the China Health and Retirement Longitudinal Study, a national survey of adults aged 45 years or over. Waist circumference was categorized into three groups: normal, pre-central obesity, and central obesity. We classified BMI into four categories: underweight, normal weight, overweight, and obese. The primary endpoint was the incidence of self-reported hearing loss. Results Of the 14,237 participants, 1972 incidents of hearing loss were identified during a median 6.9 years of follow-up. The cumulative incidence of hearing loss was 13.9% (95% CI 13.3% -14.4%). Our study showed that central obesity was significantly associated with hearing loss (HR 0.84, 95%CI 0.75–0.94), and this relationship was more prominent in males (HR 0.76, 95%CI 0.63–0.91). Among male participants, the underweight group was at the highest risk of hearing loss (HR 1.39, 95%CI 1.08–1.79). Compared with the normal weight group, the adjusted HR for hearing loss in the obese groups was 0.69 (95%CI 0.51–0.94) among men. Among female participants, only the overweight group had a lower risk of hearing loss than the normal weight group (HR 0.83, 95%CI 0.71–0.96). Conclusions Being overweight and obese were significantly associated with a decreased risk of hearing loss, whereas being underweight was associated with an increased risk of hearing loss.